2019
DOI: 10.3390/fermentation5020035
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Diverse Carbon Sources and Cultivation Conditions for Enhanced Growth and Lipid and Medium-Chain Fatty Acid (MCFA) Production by Mucor circinelloides

Abstract: Keywords: Mucor circinelloides; microbial lipids; medium-chain fatty acids; culture optimization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In another study, Senit et al and Bustamante et al calculated the composition of orange peel to be 18.9 ± 0.2% cellulose and 14.6 ± 0.2% hemicellulose, which was similar to our results [39,40]. As carbohydrates are correlated with fermentation, enzymatic hydrolysis was performed to separate monosaccharides for microbial growth using complex structures such as cellulose and hemicellulose [41,42]. Enzymatic hydrolysis using the non-pretreatment group resulted in approximately 25.0% glucan content (GC) and 36.0% ED.…”
Section: Characterization Of Orange Peelsupporting
confidence: 86%
“…In another study, Senit et al and Bustamante et al calculated the composition of orange peel to be 18.9 ± 0.2% cellulose and 14.6 ± 0.2% hemicellulose, which was similar to our results [39,40]. As carbohydrates are correlated with fermentation, enzymatic hydrolysis was performed to separate monosaccharides for microbial growth using complex structures such as cellulose and hemicellulose [41,42]. Enzymatic hydrolysis using the non-pretreatment group resulted in approximately 25.0% glucan content (GC) and 36.0% ED.…”
Section: Characterization Of Orange Peelsupporting
confidence: 86%
“…Photosynthesis is the main purpose of plants, empowering them to convert light energy into chemical energy, which is next utilized in all cell activities, and it is highly altered by pathogenic infection [ 72 , 74 ]. This decreases in chlorophyll pigments can be explained by Choudhury and Panda, Jahan et al and Singh et al [ 75 , 76 , 77 ]; they mentioned that the decrease in chlorophyll is a result of oxidative stress after injury due to the release of free radicals, causing damage or distortion in the formation of chloroplasts, and this means the failure or inability of the plant to capture light and carry out the process of photosynthesis. Moreover, data showed that the treatment with M. circinelloides strain exhibited the most potent effect in terms of the chlorophyll a contents, followed by treatment with P. oxalicum , A. flavus and A. niger.…”
Section: Discussionmentioning
confidence: 99%
“…To select mutants that impulsively eliminate the pyrF marker gene (encodes for uracil biosynthesis), 5-fluoroorotic acid (2.5 mg/mL) was added to the YPG medium [ 49 ]. All the mutant (i.e., Mu-TE+, the strain harboring the TE-over-expressing plasmid, hereafter referred to as M-1; Mu-TE+, [ acoxΔ ], the strain harboring the TE-over-expressing plasmid and exhibiting the disrupted allele for the ACOX gene, hereafter referred to as M-2; and Mu-TE+ [ acoxΔ , acotΔ ], the strain harboring the TE-over-expressing plasmid and exhibiting the disrupted allele for ACOX and ACOT genes, hereafter referred to as M-3) and the wild-type (used as the control, hereafter referred to as WT) strains of M. circinelloides (MU758) were initially cultivated by using 80 μL spore suspension (~10 7 spores/mL) in 1.0-L flasks containing 150 mL of Kendrick and Ratledge medium (K and R); 30 g/L glucose, 3.3 g/L diammonium tartrate, 7.0 g/L KH 2 PO 4 , 2.0 g/L Na 2 HPO 4 , 1.5 g/L MgSO 4 ·7H 2 O, 1.5 g/L yeast extract, 0.1 mg/L CaC1 2 ·2H 2 O, 8 mg/L FeC1 3 ·6H 2 O, 1 mg/L ZnSO 4 ·7H 2 O, 0.1 mg/L CuSO 4 ·5H 2 O, 0.1 mg/L CO (NO 3 )·6H 2 O and 0.1 mg/L MnSO 4 ·5H 2 O, pH 6.0) [ 4 , 9 , 16 , 17 , 51 , 52 , 53 ]. Subsequently, these flasks were equipped with baffles to improve aeration and finally placed in a shaker at 150 rpm at a temperature of 26 °C for 24 h. the resultant seed culture was used for inoculation at 10% ( v / v ) into a 5-L fermenter (BioFlo/CelliGen 120, New Brunswick Scientific, Edison, NJ, USA) containing 1.5 L of modified K and R medium (i.e., 80.0 g glucose/L plus inorganic salts, 2.0 g diammonium tartrate).…”
Section: Methodsmentioning
confidence: 99%